The romantic : the real life of Cashel Greville Ross : a novel - Boyd, William, 1952- (Alfred A. Knopf, 2023)
"From the award-winning, internationally bestselling author, a romp of a novel, at once intimate and panoramic, about the adventures and misadventures of a 19th-century zelig. One man, many lives ... Cashel Greville Ross experiences more of everything than most, from the rapturous to the devastating, from surprising good luck to unexpected loss. Born in 1799, Cashel seeks his fortune across the turbulence of multiple continents, from County Cork to London, from Waterloo to Zanzibar, embedded with the East Indian Army in Sri Lanka, sunning himself alongside the Romantic poets in Pisa. He travels the world as a soldier, a farmer, a felon, a writer, even a father. And he experiences all the vicissitudes of existence, including a once-in-a-lifetime love that will haunt the rest of his days. In the end, his great accomplishment is to discover who he truly is-which is the romance of life itself, and the beating heart of The Romantic"--